2021
DOI: 10.3390/su13158637
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Trans-Regional R&D Strategy for the South Korea Green New Deal to Achieve Future Mobility

Abstract: In response to the COVID-19 pandemic, South Korea is moving to establish a national industry strategy to reduce regional inequalities within the country through the Green New Deal. Thus, it is important to closely integrate the aim of reducing greenhouse gas emissions from the Green New Deal with that of reducing deepening regional inequality from the Regionally Balanced New Deal. To accomplish these dual aims, this study provides a collaborative trans-regional R&D strategy and a precise framework with thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 52 publications
(113 reference statements)
0
20
0
Order By: Relevance
“…Thus, a long-term commitment to public support and funding toward green R&D is required to accomplish the transition to the hydrogen economy [7,15], as supported by the need for an R&D investment and collaboration framework, which considers the trends of the investment and R&D spectra of the hydrogen-economy-related technology segments of the value chain of the hydrogen economy, to promote the government's commitment. Moreover, as emphasized in our previous study [54], the framework would also present the information on the regional variations that are caused by differences in the endowment of relevant assets, although it is challenging to reduce the regional inequality via a transregional research collaboration approach. In our last study [54], we proposed the transregional collaboration framework and demonstrated it with a sample of future mobility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, a long-term commitment to public support and funding toward green R&D is required to accomplish the transition to the hydrogen economy [7,15], as supported by the need for an R&D investment and collaboration framework, which considers the trends of the investment and R&D spectra of the hydrogen-economy-related technology segments of the value chain of the hydrogen economy, to promote the government's commitment. Moreover, as emphasized in our previous study [54], the framework would also present the information on the regional variations that are caused by differences in the endowment of relevant assets, although it is challenging to reduce the regional inequality via a transregional research collaboration approach. In our last study [54], we proposed the transregional collaboration framework and demonstrated it with a sample of future mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as emphasized in our previous study [54], the framework would also present the information on the regional variations that are caused by differences in the endowment of relevant assets, although it is challenging to reduce the regional inequality via a transregional research collaboration approach. In our last study [54], we proposed the transregional collaboration framework and demonstrated it with a sample of future mobility. However, it is necessary to elaborate the previously proposed framework to present more valuable information about the R&D-spectrum-based research collaboration among academia, research institutes, and industries in Korea, thus establishing a systematic approach for creating a new green value chain for the hydrogen economy by combining the existing innovative capabilities of various research organizations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations